(untitled) (Conferencea, 2023)
This article talks about the game form of physical education classes in higher educational institutions, which contributes to the formation of educational motivation in all students for physical education in general, and in combination with other educational means represents the basis for the stage of formation of a harmoniously developed, active personality, combining physical development and physical perfection.